Differential proliferation effects after short-term cultivation of mouse spermatogonial stem cells on different feeder layers - Azizi, Hossein; Hamidabadi, Hatef Ghasemi; Skutella, Thomas (Cell journal (Yakhteh), 2019)
Objective: Spermatogonial stem cells (SSCs) provide the cellular basis for sperm production transforming the male's genetic information to the next generation. We aimed to examine the effect of different feeder layer on proliferation of SSCs. Materials and Methods: In this experimental study, we compared the in vitro effects of the co-culture of mouse SSCs with mouse embryonic fibroblasts (MEFs), sandos inbred mice (SIM) embryo-derived thioguanine- and ouabain-resistant (STO) feeders, and neonate and adult testicular stroma cell (TSC) feeders on the efficiency of mouse SSC proliferation and colony formation. Cells were cultivated on top of MEFs, STO, and neonate and adult TSCs feeder layers for 30 days. The number and diameter of colonies and also the number of cells were evaluated during day 7, 15, 25, and 30 of culture. The mRNA expression of germ cells and somatic cells were analyzed. Results: In our study, we observed a significant difference in the proliferation rates and colony size of SSCs among the groups, especially for MEFs (P<0.05). SSCs can proliferate on MEFS, but not on STO, neonate or adult TSCs. Using immunocytochemistry by KI67 the proliferative activities of SSC colonies on MEFs were confirmed. The results of Fluidigm real-time polymerase chain reaction (RT-PCR) showed a high expression of the germ cell genes the promyelocytic leukemia zinc finger protein (PLZF), deleted in azoospermia-like (DAZL), octamer-binding transcription factor 4 (OCT4), and DEAD (Asp-Glu-Ala-Asp) box polypeptide 4 (DDX4 or VASA) in SSCs, and a low expression of these genes in the feeder layers. Furthermore, we observed a higher expression of vimentin and integrin-B1 in feeder layers than in SSCs (P<0.05). Conclusion: Based on the optimal effect of MEFs for better colonization of SSCs, these feeder cells seem to be appropriate candidates for SSC cultures prior to transplantation. Therefore, it is suggested using these feeder cells for SSC cultivation.
Gesehen am 26.03.2019